Building An Animation Business : An Industry and Frim Based Perspective - Tunku Mudzaffar, Tunku Nasruan Adil (2013)
This management project looks at the challenges faced by the Malaysian animation industry and the firms operating in it. Animation is an emerging sector that has become one of the primary focuses for the Malaysian government in developing the nation’s economy. The literature presents essential information of the industry from a macro level view of the industry to a micro level view of the firms. A qualitative research method was used to uncover information of both the industry and the firms via interviews with top management of animation firms. The combination of the research and interviews reveal that the focus of animation is now development and intellectual property. The research and interviews have also uncovered potential issues that must be addressed for this industry to grow.